Chemical Comparison of White Ginseng before and after Extrusion by UHPLC-Q-Orbitrap-MS/MS and Multivariate Statistical Analysis. (7th October 2020) - Guo, Yun-Long; Wang, Yang; Zhao, Yi-Lin; Xu, Xiu-Ying; Zhang, Hao; Zhao, Cheng-Bin; Zheng, Ming-Zhu; Liu, Shu-Ying; Wu, Yu-Zhu; Liu, Jing-Sheng
Abstract : Ultrahigh-performance liquid chromatography Quadrupole-Orbitrap tandem mass spectrometry (UHPLC-Q-Orbitrap-MS/MS) was used to compare the composition of ginsenosides in white ginseng (WG) and extruded white ginseng (EWG). A total of 45 saponins, including original neutral ginsenosides, malonyl-ginsenosides, and chemical transformation of ginsenosides, were successfully identified in both WG and EWG. Multivariate statistical analyses including supervised orthogonal partial least squared discrimination analysis (OPLS-DA) and hierarchical clustering analysis (HCA) were used to analyze components of white ginseng before and after extrusion. As a result, three ginsenosides (malonyl (M)-Rb1, M-Rb2, and M-Rc) were found to be increased in WG, while three ginsenosides (Rb2, Rc, and Rg1) were elevated in EWG. In the OPLS-DA S-plot, the different compositions of ginsenoside that were distinguished between WG and EWG were screened out. Experimental results indicate that the UHPLC-Q-Orbitrap-MS/MS is a useful tool to characterize variations of ginsenosides in WG and EWG.